Chlorhexidine dressings could reduce external ventricular drain infections: results from a systematic review and meta-analysis. (November 2021) - Waqar, M.; Chari, A.; Islim, A.I.; Davies, B.M.; Fountain, D.M.; Larkin, S.; Jenkinson, M.D.; Patel, H.C.
Summary: The incidence of external ventricular drain (EVD) infections remains high. Chlorhexidine dressings have demonstrated efficacy in reducing infections associated with indwelling catheters at other body sites, although evidence for their use with EVDs is limited. The aim of this systematic review and meta-analysis was to evaluate the efficacy of chlorhexidine dressings in reducing EVD-associated cerebrospinal fluid infection (EVDAI). MEDLINE, EMBASE and the Cochrane library were queried for articles from inception. The primary outcome was the incidence of EVDAI. Secondary outcomes included device safety, microbiological outcomes and shunt-dependency. From 896 unique records, five studies were included of which four presented suitable data for quantitative analysis including three case series and one underpowered randomized controlled trial. There was a high risk of bias in all studies. A total of 880 patients were included with a mean age of 57.7 years (95% confidence interval (CI) 57.4–58.0 years). In primary outcome analysis, the chlorhexidine dressing group had a significantly lower incidence of EVDAI (1.7% vs 7.9%, risk difference (RD) = 0.07, 95% CI 0.00–0.13, P =0.04). In conclusion, chlorhexidine dressings may reduce the incidence of EVDAI but require future study in randomized trials to definitively determine efficacy.